Pietro Maria Militello and Hakan Öniz (eds) SOMA 2011. Proceedings of the 15th Symposium on Mediterranean Archaeology, held at the University of Catania 3-5 March 2011 - Gallou, Chrysanthi (Journal of Greek Archaeology, 2017)
This 2-volume publication presents the proceedings of the 15th Symposium on Mediterranean Archaeology (SOMA), held at the University of Catania on 3–5 March 2011, and publishes 134 contributions, mainly from PhD students and early career researchers. The papers are primarily sub-divided into thematic groups and a broad geographical subdivision has been adopted throughout to accommodate, according to the editors, the variety of material and approaches presented.